Gambaran Penerapan Pendokumentasian Asuhan Keperawatan Berbasis Elektronik - Nurain Ino; Nanang R. Paramata; Moh. Nisyar Sy. Abd. Azis (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the implementation of electronic nursing care documentation in the inpatient wards of Toto Kabila Regional Hospital. A quantitative, non-experimental, descriptive approach was used, with a sample of 142 nurses. The results showed that the majority of respondents rated the implementation of electronic nursing care documentation as good (108 respondents; 76.1%), while a minority rated it as fair (34 respondents; 23.9%). The best implementation was in the Urology Surgery Room with the highest mean score of 1.91, while the lowest was in the Isolation Room with a mean score of 1.59. In conclusion, the majority of nurses (76.1%) rated the implementation of electronic nursing care documentation at Toto Kabila Regional Hospital as good. In conclusion, although some (23.9%) encountered technical and training challenges, all respondents (100%) stated that the system was effective and beneficial, particularly for rapid data access, efficiency, team coordination, and accuracy, thus supporting improved nursing care quality.   Keywords: HOT FIT, Electronic Nursing Care Documentation, Inpatient Nurses